2009
DOI: 10.1155/2009/573924
|View full text |Cite
|
Sign up to set email alerts
|

Face to Face: Anthropometry‐Based Interactive Face Shape Modeling Using Model Priors

Abstract: This paper presents a new anthropometrics-based method for generating realistic, controllable face models. Our method establishes an intuitive and efficient interface to facilitate procedures for interactive 3D face modeling and editing. It takes 3D face scans as examples in order to exploit the variations presented in the real faces of individuals. The system automatically learns a model prior from the data-sets of example meshes of facial features using principal component analysis (PCA) and uses it to regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…• National status of identifying aggression among the children by facial anthropometry: In a study it has been showed that pre pubertal growth can be assessed by facial anthropometry and can be milestones in analyzing behavior or changing behavior (Magdalena, 2014) Testosterone is the hormone responsible for aggression amongst the male population even in the children and the anthropometric parameter 2D and 4D ratio is said to be responsible for supporting the level of testosterone. Even the chelion a Farka's landmark had already shown similar effect like 2D/4D ratio (Zhangh, 2009) With extended study of several biomarkers corticosterone come out from the groove, at potentially subjected to increase or decrease stress amongst the person. Whereas initiation of stress brings up several other psychological abnormalities like; anxiety, depression and in further aggression.…”
Section: • Crimes and Evidences In Childrenmentioning
confidence: 98%
“…• National status of identifying aggression among the children by facial anthropometry: In a study it has been showed that pre pubertal growth can be assessed by facial anthropometry and can be milestones in analyzing behavior or changing behavior (Magdalena, 2014) Testosterone is the hormone responsible for aggression amongst the male population even in the children and the anthropometric parameter 2D and 4D ratio is said to be responsible for supporting the level of testosterone. Even the chelion a Farka's landmark had already shown similar effect like 2D/4D ratio (Zhangh, 2009) With extended study of several biomarkers corticosterone come out from the groove, at potentially subjected to increase or decrease stress amongst the person. Whereas initiation of stress brings up several other psychological abnormalities like; anxiety, depression and in further aggression.…”
Section: • Crimes and Evidences In Childrenmentioning
confidence: 98%
“…Some researchers have established a guide to map the 3D face meshes in question to a template that resembles an anthropometric mask [148]. The open-source MeshMonk tool is a script designed to automatically quantify the dense surfaces of the biological phenotypes in question.…”
Section: Face Masking and Quasi-landmarksmentioning
confidence: 99%
“…CI = Confidence interval. NR: Not reported [144][145][146][147][148][149][150][151][152][153][154][155][156][157][158][159][160][161]163,168]. Table S4: Summary of data obtained from NHGRI-EBI GWAS Catalog for SNPs that met the genome-wide significance p-value threshold of (5 × 10 −8 ) for traits in the nose region.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…It is traditional & popular methods to interact with students which are based on direct meeting on daily bases and distributing the curriculum by face to face lectures while using or supporting electronic mechanisms in the classroom used casually for students to complete their certain tasks, (Zhang and Prakash, 2009).…”
Section: Face To Face Modelmentioning
confidence: 99%